Efficient Agrobacterium mediated genetic transformation of CRISPR/Cas9 construct using cotyledonary node explants of greengram - Talakayala, Ashwini; Dokka, Narasimham; Baloji, Gugulothu; Ankanagari, Srinivas; Garladinne, Mallikarjuna (Journal of Agriculture and Applied Biology, 2023)
An efficient protocol for generating transformed greengram plants by choosing prominent explant which is used to generate transformed plantlets for their survivability and also with high transformation efficiency. However, the crop production is reduced due to factors. In current work, we employed transgenic free approach using CRISPR/Cas9 tool for establishing transformation protocol. The CRISPR/Cas9 is getting momentum widely for developing transgene free crops. In this approach, guide RNA encoding for ~18-23 bp sequence that contains a PAM (protospacer adjacent motif) on either strand of DNA, where CRISPR incepts with a single guide RNA (sgRNA) to target genes and initiate excision of a complimentary strands through the Cas9 endonuclease. Explants’ effects on CRISPR/Cas9 construct transformation were studied. For transformation, three distinct explants cotyledonary node (CN- MSB5 +3% sucrose+ 0.5 mg/L BAP for CN), shoot tip (ST- MSB5 + 3% sucrose+ + 0.5 mg/L BAP + 0.01 mg/L NAA), and immature cotyledon (IMC-3% sucrose + 0.5 mg/L BAP + 0.1 mg/L NAA) were used. The prepared explants were infected with EHA105 strain of Agrobacterium tumefaciens harboring a binary vector of pMDC100 containing npt II gene as screenable marker and Cas9. The explants were selected on 50 mg/L kanamycin medium. The transformed plants were confirmed by PCR using npt II and Cas9 specific primers. Cotyledonary node explant was found to be more efficient for CRISPR/Cas9 transformation and also it promisingly showed transgene integration through PCR analysis having more transformation efficiency and can be used for the production of transgenic free greengram crop using CRISPR/Cas9 approach.